Inefficient Worker Turnover - JACQUET, Nicolas Laurent (Institutional Knowledge at Singapore Management University, 2006)
This paper considers the efficiency properties of risk-neutral workers' mobility decisions in an equilibrium model with search frictions, but no search externalities, when the rent accruing to a match is split through bargaining. Matches are ex ante homogeneous and their true productivity is learnt after the match is formed. It is shown that the efficiency of worker turnover depends on contract enforceability, and that in the absence of complete enforceability the equilibrium fails to be efficient. This is because without complete enforceability firms cannot credibly offer workers contracts that will guarantee them the entire future of all potential future matches.